Characterization of 4 deletion mutants of Pseudomonas plecoglossicida and their potential for live attenuated vaccines in large yellow croaker (Larimichthys crocea). Issue 127 (August 2022) - Li, Yiying; Chi, Yu; Li, Shanshan; Jia, Tingting; Mao, Zhijuan
Abstract: To search for live attenuated vaccines (LAV) candidates against Pseudomonas plecoglossicida, the causative agent of the visceral granulomas disease in farmed large yellow croaker ( Larimichthys crocea ), two type Ⅵ secretion systems (T6SS) and a predicted α/β fold family hydrolase encoding gene, ORF4885 were targeted to construct deletion mutants. The biological profiles of 4 mutants were characterized; LD50 to the croakers detected, in vivo survival post-infection investigated， relative percent of survival (RPS) of the croakers 28d post-vaccination determined, and transcription of five immunity-related genes of the treated fish was quantified. On comparison to the WT, the mutants revealed similar growth curves in 11h; swarming motility of Δ4885 declined significantly at 72h post-incubation (P < 0.05); ΔS1Δ4885 showed significantly poor biofilm formation and weak resistance to fish serum bactericidal activity (P < 0.05). LD50 of the mutants were much higher than the WT, indication of strong virulence attenuation; in vivo survival test showed the mutant ΔS1Δ4885 and ΔS1ΔS3 were eliminated by the host 10d post-infection, demonstration of the safety and potentiality to be LAV candidates. Immunization with the mutant ΔS1Δ4885 provided higher RPS than ΔS1ΔS3. Transcription of IgT was significant in all immunized groups while IgM increased only in intraperitoneally injected groups. This study successfully searched a quite safe and strong immunogenic LAV candidate to defeat P. plecoglossicida infection. Highlights: Constructed three deletion mutants of P.plecoglossicida . Biological profiles of four mutants changed. Two virulence attenuated strains survived in the croakers but were cleared in 10 days. Two LAV candidates stimulated immunity response and provide significant protection.